European perspective of perampanel response in people with Intellectual Disability. (26th May 2020) - Allard, Jon; Henley, William; Snoeijen‐Schouwenaars, Francesca; van Ool, Jans; Tan, In; Jurgen Schelhaas, H.; Majoie, Marian H. J. M.; Hudson, Sharon; McLean, Brendan; Shankar, Rohit
Abstract : Background: Epilepsy prevalence is over 20% for those with ID. It is difficult to diagnose and treat and more likely to be treatment resistant. The evidence informing prescribing is sparse, particularly for new drugs such as perampanel (PMP). Aims of the Study: This study seeks to strengthen the research evidence regarding PMP for people with ID by pooling information from two isolated and separately conducted studies: the UK‐based Epilepsy Database Register (Ep‐ID) and the data from the Kempenhaeghe clinic in the Netherlands. Methods: A single data set of comparable data was created and analysed under agreement and supervision of a UK statistician. Results: Seizure reduction within twelve months was evident in 62% of Dutch and 47% of UK patients. Retention rates were higher for those in the UK ( P  = .01) and for patients with moderate to profound ID, whilst side effects were more prominent in the Dutch cohort. Conclusions: Comparable rates of seizure reduction are in line with estimates for non‐ID patients, adding to the evidence suggesting that PMP has a similar impact on those with ID. Taking a European perspective and sharing data across centres can help strengthen the evidence for prescribing antiepileptic drugs in the ID population.